In Vitro Evaluation of Apical Sealing Ability of HEROfill® Obturator versus Cold Lateral Condensation in Curved Root Canals - Mina Zarei; Maryam Javidi; Zeinab Kazemi; Farzaneh Afkhami (Tehran University of Medical Sciences, 2016)
Objectives: This study aimed to assess and compare the apical sealing ability of HEROfill® Soft-Core system and lateral condensation technique in fine curved canals using the fluid filtration method. Materials and Methods: Forty human mesiobuccal root canals of mandibular first molars with 25° to 40° curvatures were instrumented to an apical size 30/0.04. Roots were randomly assigned to two experimental groups of 15, designated as groups A and B. Two control groups, each containing five teeth, served as positive and negative controls. Group A was obturated using lateral condensation technique and group B with the HEROfill® Soft-Core system. The groups were tested for microleakage using an in vitro fluid filtration apparatus with 0.5 atm pressure at zero, two, four, six, eight and 10 minutes. Independent t-test was used to analyze the microleakage data. Results: The mean and standard deviation (SD) values for fluid microleakage in the lateral condensation group were 0.58±0.49 µL/min, 0.68±0.35 µL/min, 0.74±0.22 µL/min, 0.71±0.29 µL/min and 0.60± 0.29 µL/min at two, four, six, eight and 10 minutes, respectively. The mean and SD values for fluid microleakage in the HEROfill® group were 0.53±0.42 µL/min, 0.67±0.34 µL/min, 0.69±0.26 µL/min, 0.73±0.33 µL/min and 0.63±0.26 µL/min at two, four, six, eight and 10 minutes, respectively. The difference between the lateral condensation and HEROfill® groups was not statistically significant at two (P=0.776), four (P=0.909), six (P=0.562), eight (P=0.861) or 10 (P=0.765) minutes. Conclusion: The HEROfill® system and cold lateral condensation technique were equally effective for apical sealing of curved canals.